Resenha bibliográfica - Maurício Chalfin Coutinho (Universidade de São Paulo, 2010)
MURPHY, Antoin E. The genesis of Macroeconomics – new ideas from Sir William Petty to Henry Thornton. Oxford: Oxford University Press, 2009. 234 p.